Corpulações: Informação, Comunicação, Movimento e contato - Queiroz, Clélia Ferraz Pereira de (2006)
The subject-matter of this thesis is the role played by movement and contact in the processes of communication. The present research proposes the hypothesis that movement is information and perception, which turns the body into a Corpusmedia (the body as a communication medium). The close relationship between movement and contact plays a fundamental role in the developmental processes of the organism. In order to understand how the body is implied in communication, research on this matter must take recourse to the cognitive sciences. In order to sustain that movement is information and perception, it is necessary to explain the relations and implications of movement and contact within information networks and bodyenvironment communication. The aim of this research is to understand movement and contact as language in a non hierarchic information and communication network, bound to compromise a new epistemology as a applied science of the body. Within the Communication and Semiotic Program at the São Paulo Catholic University, semiotic theories, cognitive science and sciences of complexity are theories of excellence and the most appropriate field to comprehend this phenomena and form the theoretical frame of reference. Corpusmedia, designed to cover all the communication processes, developped both by Phd Professors Christine Greiner & Helena Katz, is the foundation to approach the body within the field of communication, as presented herein. This endeavor is the basis upon which the necessary conditions arise to carry out research on the body within the communication field. With the Semiotic concept of Corpusmedia, the technical term mídia differs from its common meaning. The medium and midiatic concepts in the information society many times reproduce in their core the bodymachine metaphor, which is so widely disseminated in Mass Media consumption society. According to this metaphor understanding of the communication processes sustain a mechanicist, dualist and reductionist view, one which fails to explain all the body-environment processes. The need to focus the question of movement and contact on communication, derives from the fact that available literature on this issue approaches the body as an information-processing machine. The present study sustains that by regarding the body as Corpusmedia, we escape from dualistic formulations and from those which imply that the body is disposable and replaceable, since it is considered as an object and a reproducer under the body-machine metaphor. The point here is to approach the body as a producer of knowledge. This research, starting from theoretical-praxis processes, explored communication through the cognition processes of the body. For this purpose, it was fundamental to count on the theories of neurodarwinism of Gerald Edelman, and the dynamic theory of Esther Thelen. Supported by these views, it was possible to research outside the common nature versus nurture split that gets in the way of understanding communication as an evolutive feature of the body